Evaluation Of Performance Appraisal Practices and Organisational Justice Towards Work-Related Outcomes: A Case Study of a Malaysian Government Agency in The Northern Region - Mohd Pauzi, Muhammad Faris; Baba Rahim, Norizan (Universiti Utara Malaysia Press, 2023)
Performance appraisal practices and work-related outcomes have become a serious matter of concern to many organisations. These issues would jeopardise the employees’ well-being if there is no fairness in treatment in the organisation. As a result, this research aims to evaluate the effect of performance assessment practices on work-related outcomes, with organisational justice serving as a mediator. This research examined a randomly selected sample of 127 administrative employees from a Malaysian government institution located in the northern region. It examined the relationships between performance assessment practices and organisational justice, work performance, work deviant behaviour and the mediating consequences of organisational justice on these linkages. The research model was tested based on the Social Cognitive Theory. Results from the Partial Least Squares Structural Equation Modelling (PLS-SEM) indicated that performance assessment practices positively impacted organisational fairness and work performance. The results suggest that organisational fairness mediates the correlation between the work-related deviant behaviour and the impact of performance assessment practices on work performance. Looking at the study’s findings, enforcing HR practices would gain positive favour among its employees, who are vital assets in executing the organisation’s agenda. As a result, the transformation programme will be more aligned, allowing it to continue providing talent to the economy by improving its performance through its employees.